1986
DOI: 10.3382/ps.0651400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sperm Numbers per Insemination Following Early or Late Initial Inseminations in Turkeys

Abstract: Large White turkey hens were used in this study to investigate sperm storage in the hen throughout a 20-week breeding cycle. Hens were initially inseminated early or late and subsequently at 7-day intervals with either 20, 50, or 100 million sperm each time. Early inseminations (EI) were performed on Days 14 and 17 postlighting, and the late inseminations (LI) were performed on Days 21 and 24 postlighting. Fertility (percent) was calculated weekly for 20 weeks following the second initial insemination in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…When storage sites were filled in the 50m or 100m treatments, acceptable fertility was noted early in the laying cycle; however, as hens aged, fertility fell to unacceptable levels, and hens relied more on spermatozoa from initial AI for fertility. The fact that AI of 50 million cells/ wk failed to maintain adequate fertility contradicts the hypothesis of Mclntyre et al (1986), that storage capacity of the oviduct may be 50 million cells/wk following initial AI that fills the oviduct. Because 50m treatment hens relied more than 200m treatment hens on spermatozoa from initial AI for fertility, Christensen's (1981) hypothesis that subsequent AI act to keep spermatozoa in storage sites is supported.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…When storage sites were filled in the 50m or 100m treatments, acceptable fertility was noted early in the laying cycle; however, as hens aged, fertility fell to unacceptable levels, and hens relied more on spermatozoa from initial AI for fertility. The fact that AI of 50 million cells/ wk failed to maintain adequate fertility contradicts the hypothesis of Mclntyre et al (1986), that storage capacity of the oviduct may be 50 million cells/wk following initial AI that fills the oviduct. Because 50m treatment hens relied more than 200m treatment hens on spermatozoa from initial AI for fertility, Christensen's (1981) hypothesis that subsequent AI act to keep spermatozoa in storage sites is supported.…”
Section: Discussionmentioning
confidence: 74%
“…An AI tech- Mclntyre et al (1982) proposed that AI could be more efficient if spermatozoa storage sites of the turkey hen were filled initially. In a subsequent study, Mclntyre et al (1986) proposed that filled storage tubules may release newer stored cells more readily. When storage sites were filled in the 50m or 100m treatments, acceptable fertility was noted early in the laying cycle; however, as hens aged, fertility fell to unacceptable levels, and hens relied more on spermatozoa from initial AI for fertility.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Artificial insemination (AI) of turkey hens before the onset of egg production generally results in higher hen fertility than in hens inseminated initially after the onset of egg production (Mclntyre et al, 1982(Mclntyre et al, , 1986. Although the physiological basis of these observations has not been established, Mclntyre et al (1982) suggested that there is "... an increased receptiveness of the hen's oviduct to spermatozoa during the time that natural mating frequency is highest".…”
Section: Introductionmentioning
confidence: 99%